Main N6-Methyladenosine Readers: YTH Family Proteins in Cancers - Dai, Xin-Yuan; Shi, Liang; Li, Zhi; Yang, Hai-Yan; Wei, Ji-Fu; Ding, Qiang (Frontiers in Oncology, 2021)
Among the over 150 RNA modifications, N6-methyladenosine (m6A) is the most abundant internal modification in eukaryotic RNAs, not only in messenger RNAs, but also in microRNAs and long non-coding RNAs. It is a dynamic and reversible process in mammalian cells, which is installed by “writers,” consisting of METTL3, METTL14, WTAP, RBM15/15B, and KIAA1429 and removed by “erasers,” including FTO and ALKBH5. Moreover, m6A modification is recognized by “readers,” which play the key role in executing m6A functions. IYT521-B homology (YTH) family proteins are the first identified m6A reader proteins. They were reported to participate in cancer tumorigenesis and development through regulating the metabolism of targeted RNAs, including RNA splicing, RNA export, translation, and degradation. There are many reviews about function of m6A and its role in various diseases. However, reviews only focusing on m6A readers, especially YTH family proteins are few. In this review, we systematically summarize the recent advances in structure and biological function of YTH family proteins, and their roles in human cancer and potential application in cancer therapy.